Candida in potentially malignant oral disorders - S Leena Sankari; K Gayathri; N Balachander; L Malathi (Wolters Kluwer Medknow Publications, 2015)
Oro-pharyngeal cancer is a significant component in the global burden of cancer. A considerable proportion of oral squamous carcinomas develop from preexsiting potentially malignant disorder of the oral cavity. The term potentially malignant oral disorders (PMD) were proposed for the precancerous lesions and conditions by World Health Organization in 2007. PMD are considered an in-between clinical state, which showed increased risk for cancer development. Etiology of PMD is multifactorial. Tobacco and alcohol are the major risk factors. In recent years, role of candidal infection is recognized as a significant factor in the development of PMD. There is an enduring discussion whether Candida infection can be a cause of PMD or a superimposed infection in a preexisting lesion. This article highlights the association between Candida and PMD.